Feasibility Study Of Subsea Pipeline Crossing Plan - Taufiqur Rachman (Collaborate Engineering Daily Book Series, 2023)
With so many pipelines being built, there is a big possibility that one pipeline will cross another pipeline. Crossing pipes between existing and new pipes can be avoided by creating new pipe routes. Building a new pipeline may cost additional money and time. If the new pipe route is determined to pass through the existing pipe route, then the risks posed must be analyzed because it will affect the existing pipe and the new pipe. In general, failures that occur in pipes are due to the design of pipe wall thickness, pipe stability design, pipe free span design, and pipe stress design when installed using pipelay vessels that are not safe and efficient. Pipe wall thickness design based on the DNV-OS F101 standard explains that the pipe design thickness must be sufficient to withstand working loads such as environmental loads and system pressure. Pipe stability design based on DNV-RP F109 and DNV-RP E305 explains that the pipe design must be in a stationary condition due to vertical and lateral loads. So, several of these references are used to design the crossing pipeline.